Effects of bromide-enriched natural seawater culture medium on protein and monoterpenes output of Ochtodes secundiramea (Rhodophyta, Gigartinales) - Machado, Levi P. [UNESP]; Stefanello, Eliezer; Andreghetti, Daniel X.; Zambotti-Villela, Leonardo; Colepicolo, Pio; de Carvalho, Luciana R.; Yokoya, Nair S. (Springer Nature, 2019)
Benthic marine algae, especially Rhodophyta, are within a well-known marine group able to produce secondary metabolites with bioactive properties. Among them are halogenated terpenes, synthesized by vanadium-dependent haloperoxidase (V-BPO). The red alga Ochtodes secundiramea (Montagne) M. Howe produces high amounts of halogenated monoterpenes (HMT) which have the potential to control phytopathogenic fungi. Culture closed a system is a tool used to manipulate conditions to increase the synthesis of HMT and other metabolites. The apical segments of O. secundiramea were cultivated in a bioreactor, either in seawater enriched with half strength von Stosch’s solution (VSES/2) without (control) and with the addition of 250 mg L−1 bromine (treatment). In response to these conditions, specific growth rate, HMT profile, soluble protein, phycobiliproteins, soluble carbohydrate, and chlorophyll as well as the V-BPO activity, uptake, and accumulated bromine within the biomass were evaluated. The treatment did not promote significant alterations in the growth but increased the V-BPO activity and bromine uptake and incorporation (2.5 fold). No changes in the HMT profiles of the extracts from both cultures conditions were observed by gas chromatography–mass spectrometry analyses, whereas the values of total soluble protein and phycobiliproteins were 2-fold higher in samples from the bromine-enriched medium when compared to samples from control. These results support the evidences of protective effects promoted by V-BPO activity. Furthermore, carbohydrate and chlorophyll contents were not affected by experimental conditions. These results provided new low-cost strategies that can be applied to increase of certain biomass components, which here are algal proteins, especially in Rhodophyta-based biotechnological industries for food and agriculture.
Keywords: Antifungal; Bioreactor; Bromoperoxidase; Halogenated monoterpenes; Protein content; Rhodophyta